Currency hierarchy and underdevelopment - Hansjörg Herr; Zeynep Nettekoven (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2022)
Money in capitalism is a social force which exists not only on the level of wealth owners, but is also a force which stimulates economic development (or fails to do so). According to Hajo Riese the asset-protecting function of money, which can be expressed in a liquidity premium, indicates different qualities of money. At the top of the hierarchy are a small number of currencies which take over national and international functions; at the bottom are currencies which only partly take over national functions. Countries issuing these currencies suffer from dollarisation and capital flight. The consequence is that they cannot have a strong and sustainable Schumpeterian credit–investment mechanism. External credit seems to be a solution, but external debt together with credit dollarisation leads to a fragile domestic financial system and the likelihood of overindebtedness. A poor quality of money is one key element in explaining the reproduction of underdevelopment.
Keywords: 330; currency hierarchy; dollarisation; underdevelopmentE42; F63; O16